PKM Otomatisasi Mesin Pemipil dan Penghancur Bonggol Jagung untuk Meningkatkan Kuantitas Hasil Pemipilan Jagung dan Menghasilkan Pupuk Organik Kelompok Wanita Tani Dame Ukur di Desa Boangmanalu Kecamatan Salak Kabupaten Pakpak Bharat Provinsi Sumatera Uta - Saragi, Jandri Fan HT; Boangmanalu, Eka Putra Dairi; Pratama, Angga Bahri; Sahat, Sahat (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2024)
Corn is one of the key commodities in the agricultural sector in Boangmanalu Village, Salak District, Pakpak Bharat Regency, North Sumatra Province. To support this important commodity, a faster shelling process is needed to achieve optimal results. However, the current shelling process relies on manual methods, leading to small quantities and waste from the corn cobs. The purpose of this community service activity is to increase the quantity of corn shelling results and produce organic fertilizer, thereby minimizing waste. The method used is Participatory Action Research (PAR). The results of this community service activity include partners successfully using corn cob shelling and crushing machines, an increase in the quantity of shelling results, and the production of organic fertilizer.